Glucose obtained from rice bran by ultrasound-assisted enzymatic hydrolysis (2015)
In this work ultrasound-assisted solid-state enzymatic hydrolysis of rice bran to obtain fermentable sugars was investigated. For this purpose, process variables such as temperature, enzyme concentration and moisture content were evaluated during the enzymatic hydrolysis with and without ultrasound irradiation. The enzyme used is a blend of amylases derived from genetically modified strains of Trichoderma reesei. Kinetic of the enzymatic hydrolysis of rice bran at the constant-reaction rate period were measured. The best results for the ultrasound-assisted enzymatic hydrolysis was obtained using 3 wt% of enzyme, 60 oC and moisture content of 65 wt%, yielding 0.38 g sugar/g rice bran, whereas for the hydrolysis in the absence of ultrasound the highest yield was 0.20 g sugar/g rice bran using 3 wt% of enzyme, 60 oC and moisture content of 50 wt%. The use of ultrasound-assisted enzymatic hydrolysis of rice bran was intensified, obtaining around 74% more fermentable sugar than in the absence, showing that the use of ultrasound is a promising technology to be used in enzymatic reaction as an alternative of process intensification.